2013
DOI: 10.1530/eje-13-0510
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D increases circulating IGF1 in adults: potential implication for the treatment of GH deficiency

Abstract: Objectives: Previous studies suggested that vitamin D modulates circulating IGF1. We investigated this effect in adults and its clinical relevance in the management of GH deficiency (GHD). Design and methods: IGF1 levels were prospectively measured before and after 12 weeks of treatment with oral vitamin D 3 (5000 or 7000 IU/week) vs no intervention in 39 subjects 61.9G7.9 years old. The frequency of IGF1 values R50th age-and sex-specific percentile in relation to vitamin D status, as determined by the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 25 publications
(28 reference statements)
4
64
1
3
Order By: Relevance
“…D 3 levels and are up-regulated in sera by vitamin D 3 treatment (24). Interestingly, we found that expression of Igf1, which encodes a factor that maintains tissue homeostasis (30), was significantly down-regulated in sciatic nerves and clonal Schwann cells under high glucose conditions but that its expression was rescued by either ARI or vitamin D 3 treatment (Fig.…”
Section: Increased Igf1 Expression Promoted By Vitamin D 3 Treatment mentioning
confidence: 76%
See 1 more Smart Citation
“…D 3 levels and are up-regulated in sera by vitamin D 3 treatment (24). Interestingly, we found that expression of Igf1, which encodes a factor that maintains tissue homeostasis (30), was significantly down-regulated in sciatic nerves and clonal Schwann cells under high glucose conditions but that its expression was rescued by either ARI or vitamin D 3 treatment (Fig.…”
Section: Increased Igf1 Expression Promoted By Vitamin D 3 Treatment mentioning
confidence: 76%
“…Insulin-like growth factor 1 (Igf1) is similar to insulin in structure and function and regulates various aspects of growth and development of individuals (23). Igf1 is produced primarily in the liver following growth hormone stimulation (23), and vitamin D 3 level is reportedly correlated with serum Igf1 levels (24).…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…Based on cross-sectional studies in community-based cohorts, positive correlations of vitamin D and IGF-I have been observed (36,37). Ameri et al (38) showed that vitamin D increased circulating IGF-I levels in adults and speculated that a better vitamin D status can favor the normalization of IGF-I levels in adults with treated GH deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concentration of 25OH-D3 was retrospectively assessed in 69 GHD patients on stable hormone replacement. The authors demonstrated higher IGF-I levels in GHD patients with higher 25OH-D3 levels (≥ 15 ng/ml), and a logistic regression analysis confirmed a significant positive association between ≥15 ng/ml 25OH-D3 levels and higher IGF-I [22]. Confirmatory data in healthy populations were collected by Bogazzi et al, who identified a positive relationship between serum 25OH-D3 and IGF-I concentrations in 241 healthy subjects [23], and by Hippönen et al in a large population of 6810 British adult subjects [6], concluding that 25OH-D3 status may contribute to determining serum IGF-I levels.…”
Section: Vitamin D and Igf-imentioning
confidence: 86%